Answer:
∛(16)/e
Step-by-step explanation:
The mistake made by Helen was in the last step. 2 to the power of 4/3 is equivalent to the cubic root of 2^4 instead of the fourth root of 2^3.
On the other hand, Stephen made a mistake in the first step. He replaces ln2 by 2 on the power of e and that is not equivalent.
Now, we can simplify the expression as:
![e^{(4)/(3)\ln 2-1}=\frac{e^{(4)/(3)\ln2}}{e}=\frac{e^{\ln 2\text{ \textasciicircum(4/3)}}}{e}=\frac{2^{(4)/(3)}^{}}{e}=\frac{\sqrt[3]{2^4}}{e}=\frac{\sqrt[3]{16}}{e}](https://img.qammunity.org/2023/formulas/mathematics/college/xn1wzk89g5hv2zeikgwcsznlgwd8p8109j.png)
So, the equivalent expression is:
∛(16)/e